Tivat’s urban regeneration-from arsenal to Porto Montenegro - Martinović Ksenija (Glasnik Srpskog Geografskog Društva)
This paper examines how and to what extent urban regeneration works in practice through the lens of Tivat’s regeneration. The paper enlightens Tivat’s economic and physical transformations from the town know as a base of the Naval-shipyard “Arsenal” to the nautical-touristic complex “Porto Montenegro”. Since its development in 1889, Arsenal became the main employer in town and shaped the town’s identity. Arsenal employed experienced skilled workers, mostly engineers and craftsmen, and enjoyed an international reputation for a quality ship repair (Radovic, 2015). In 1990’s, the turbulent political and economic situation in ex-Yugoslavia countries and UN sanctions resulted with a decrease of demand and the downfall of Arsenal resulted with decline of Tivat’s economy. Additionally, Montenegro was making strategic turnover from a socialist centrally planned to an open market economy. Montenegro wanted to attract inward investments and create an image of an attractive tourist destination that would result with economic revitalization. These circumstances led to the Montenegrin government decision to sell Arsenal to a private investor who showed the initiative to transform it and create the nautical resort “Porto Montenegro”. Regeneration of Tivat, in terms of its vision, seems to be a successful story - the town’s image was changed, Arsenal’s site became a part of wider urban tissue, and new economic opportunities were made. However, this regeneration did not go without negative consequences, including the displacement of skilled workers, social exclusion and missed opportunity to reintegrate the urban fabric and reconnect the town with the sea.